Kompetensi Auditor Internal Dalam Meningkatkan Kualitas Laporan Keuangan Pemerintah Daerah (Studi di Kantor Inspektorat Kota Manado - Aurelia Tamuntuan; Masje Pangkey; Helly Kolondam (JURNAL ADMINISTRASI PUBLIK, 2023)
Inspectorate of Manado City has 13 Internal Auditors in reviewing the financial statements of regional apparatus. This study was conducted to determine the competence of internal auditors in improving the quality of Manado City Regional Financial Statements. This research uses qualitative research methods with data collection techniques through observation and secondary data collection. The data is analyzed through the stages of rediction, presentation and conclusion. This study suggests that the competence of the Manado City Internal Auditors with regard to Knowledge, Skills, and Attitudes, is good but the lack of time given by the auditors to review and the Regional Apparatus Organizations (OPD) are slow to submit reports and the auditees' lack of knowledge of reporting standards, this is an obstacle for the auditor team in carrying out the review. Development and improvement of the competence of the Inspectorate Internal Auditors can be implemented by recruiting prospective members of the auditor team with an educational background and experience in the field of auditing, as well as by attending special training related to the use of the review application, as well as maintaining the professional attitude, ethics and integrity already possessed by the Internal Auditors of the Manado City Inspectorate.Abstract. Manado City Inspectorate has 13 Internal Auditors in reviewing the financial statements of regional apparatus.